TOKSISITAS LARVASIDA FRAKSI POLAR DAN NON POLAR HERBA Eclipta alba Hassk TERHADAP LARVA NYAMUK Aedes aegypti Linn - Hamidah; Rosmanida; Darmawati (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 1999)
Dengue Haemorrhagic Fever is a disease caused by virus and spread out by mosquitoes. Until now Aedes aegypti is thought as important vector in spreading procces of this disease. The general technique with synthetic chemical insecticide used to control density of mosquito population but this way causes the resistence of insect target, kill the untarget insect, and disturbs the environment quality. Due this problem, insecticide from plant is one of alternative such as Eclipta alba (Urang aring). The research aimed to distinguish toxicity larvacida degree between the polar fraction and non polar herba Eclipta alba to the growth of mosquito larva of Aedes aegypti. The experimental method applied with the complete random design used in this research. Each treatment to mosquito larvae of Aedes aegypti had replications and the data was analyzed of Variance (ANOVA). The result showed that non polar fraction has the higher toxicity effect compared with the polar fraction. The concentration of LC non polar fraction 319.1826 ppm50, and concentration LC50 polar fraction is 1033.888 ppm and instar larva change of non polar fraction give higher elimination than polar fraction, non polar is 24% from population has change into IV instar and non polar 45%.